Effects of weed management on agronomic performance and productivity of hybrid maize (Zea mays L.) - Burhanuddin Wiqar; Mohammad Safar Noori; Sayed Younos Amini (Journal of Agriculture and Applied Biology, 2021)
The yield loss as a result of weed infestation is a major problem in maize fields. Hence, this research meant to examine the impacts of weed chemical control on maize growth and yield. The design of experiment was randomized complete block, and comprised 10 treatments viz., T1 (Control, weedy check), T2 (Weed free), T3 (Atrazine 1.5 kg ha-1 pre-emergence), T4 (Atrazine 750 g ha-1 + Pendimethalin 750 ml ha-1 pre-emergence), T5 (Atrazine 1.5 kg ha-1 followed by 2,4-D amine 0.4 kg ha-1 at 25 days after sowing as Post-emergence), T6 (Halosulfuron 67 g ha-1 at 25 DAS), T7 (Atrazine 1.5 kg ha-1 pre-emergence followed by Halosulfuron 90 g ha-1 25 days after sowing), T8 (Tembotrione 120 g ha-1 Post-emergence at 25 days after sowing), T9 (Pendimethalin 1000 ml ha-1 pre-rise fb Atrazine 750 g ha-1 + 2,4-D amine 0.4 kg ha-1 at 25 days after sowing as Post-emergence) and T10 (Atrazine 1.5 kg ha-1 pre-emergence followed by Tembotrione 120 g ha-1 Post-emergence at 25 days after sowing) with 3 replicates. The results showed that among other treatments, T10 recorded highest number of kernels per row (36.18), number of kernel cob-1 (499.12) and kernel weight cob-1 (136.97 g). A higher plant height (172.19 cm), leaf area (396.6 cm2 plant-1), dry matter accumulation (211.37 g plant-1), kernel yield (6.7 t ha-1) and stover yield (11.6 t ha-1) were found with weed free check plot which is on par with T10 treatment which brought about a higher value of plant height (162.93 cm), dry weight accumulation (205.7 g plant-1), leaf area (384.3 cm2 plant-1), kernel yield (6.5 t ha-1) and stover yield (11.4 t ha-1). In the meantime, T9 treatment reasonably increased kernel yield (6.2 t ha-1) and stover yield (11.0 t ha-1). It shows that application of herbicides as pre-emergence followed by post-emergence, such as T10 treatment could be a good method for weed control in maize fields.